The ability gradient in tax responsiveness - Spencer Bastani; Daniel Waldenström (Journal of Public Economics Plus, 2021)
We study the role of cognitive ability for individuals' tax responsiveness using linked administrative tax and military enlistment registers. Our main finding is that individuals in the top decile of the ability distribution react twice as strong to a large and salient kink point in the Swedish tax code as compared to the average individual, and three times as strong as individuals in the bottom ability decile. This ability gradient is mainly driven by income shifting among high-ability owners of incorporated businesses, but we also find evidence of labor-supply responses among high-ability wage earners.
Keywords: H21; H24; J22; J24; 330; Cognitive ability; Income shifting; Labor supply; Bunching